2007
DOI: 10.1007/s00256-006-0175-4
|View full text |Cite
|
Sign up to set email alerts
|

Congenital pseudoarthrosis associated with venous malformation

Abstract: Congenital pseudoarthrosis is a pathologic entity that may be isolated, or may be associated with neurofibromatosis. We report the case of a 3-year-old female with congenital pseudoarthrosis involving the right tibia and fibula. Magnetic resonance imaging (MRI) and complementary magnetic resonance angiogram (MRA) revealed a lobulated mass with vivid enhancement, which led to the diagnosis of venous malformation. This is the first report of congenital pseudoarthrosis caused by the presence of a vascular malform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…Hermanns-Sachweh et al ( 31 ) suggested the thickened periosteum was caused by neural-like cells that form a tight sheath around the small periosteal vessels, causing narrowing or obliteration of the vessels. This results in a disturbance of the blood circulation of the periosteum, which in turn results in impaired oxygen and nutrient supply of the subperiosteal bone with subsequent fracture and recalcitrant nonunion ( 31 , 34 ). Kuorilehto et al ( 35 ) found that the arteriovenous wall thickening, lumen stenosis and vascular wall thickening, and partial obstruction of the vessels were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Hermanns-Sachweh et al ( 31 ) suggested the thickened periosteum was caused by neural-like cells that form a tight sheath around the small periosteal vessels, causing narrowing or obliteration of the vessels. This results in a disturbance of the blood circulation of the periosteum, which in turn results in impaired oxygen and nutrient supply of the subperiosteal bone with subsequent fracture and recalcitrant nonunion ( 31 , 34 ). Kuorilehto et al ( 35 ) found that the arteriovenous wall thickening, lumen stenosis and vascular wall thickening, and partial obstruction of the vessels were observed.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 CPC is described as a clinical condition that is distinct from craniocleidodysostosis (CCD), obstetric delivery difficulties birth trauma resulting in secondary fractures and neurofibromatosis. 5,6 It was documented that CPC has an association with cervical ribs with roughly 15% of diagnosed cases. 7 However, our case showed no evidence of a cervical rib.…”
Section: Discussionmentioning
confidence: 99%
“…Dependendo das condições de cultivo, as CMM da medula óssea podem se diferenciar em osteoblastos, adipócitos e condrócitos (ARVIDSON et al, 2011;GIULIANI et al, 2013 -HADIDY et al, 2007). Além disso, também pode ser uma doença congênita isolada sem associação a nenhuma doença já conhecida.…”
Section: Células Estromais Mesenquimais Multipotentes (Cmm)unclassified
“…Além disso, também pode ser uma doença congênita isolada sem associação a nenhuma doença já conhecida. (AL-HADIDY et al, 2007 ).…”
Section: Células Estromais Mesenquimais Multipotentes (Cmm)unclassified
See 1 more Smart Citation